2023
DOI: 10.1039/d2bm01878k
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic dendrimers against antibiotic resistance: light at the end of the tunnel?

Abstract: The alarming and prevailing antimicrobial resistance (AMR) calls urgently for novel antibacterial agents that are effective and stable but do not induce resistance development. Amphiphilic dendrimers are emerging as a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Due to the nanometric size with radially symmetric, mono-dispersed, and homogenous properties, dendrimers have been used in nanomedicine research. 123,124 Aside from their apparent utility as drug delivery or gene carrier systems, research has revealed that certain dendrimers have therapeutic applications of their own, primarily because of their antifungal, 125 and antibacterial, 126,127 and cytotoxic properties. 128,129 Dendrimers lie on the border between polymer and molecular chemistry.…”
Section: Redox-cleavable Star Polymersmentioning
confidence: 99%
“…Due to the nanometric size with radially symmetric, mono-dispersed, and homogenous properties, dendrimers have been used in nanomedicine research. 123,124 Aside from their apparent utility as drug delivery or gene carrier systems, research has revealed that certain dendrimers have therapeutic applications of their own, primarily because of their antifungal, 125 and antibacterial, 126,127 and cytotoxic properties. 128,129 Dendrimers lie on the border between polymer and molecular chemistry.…”
Section: Redox-cleavable Star Polymersmentioning
confidence: 99%
“…[208] Dendrimers can also be used to deliver antibiotics and increase the solubility of antibiotics. [209] Galanakou et al [210] systematically discussed the applications of amphiphilic dendrimers against antibiotic resistance. Due to the electrostatic interaction with anionic-charged bacterial surfaces, amphiphilic dendrimers with cationic charges can penetrate into the bacterial cell membrane, which leads to membrane destruction and then cause cell death.…”
Section: Other Applicationmentioning
confidence: 99%
“…14,15 In the last decade, amphiphilic dendrimers, a broad series of dendrimers of asymmetric structure that includes core-shell dendrimers, Janus dendrimers, dendron-tail dendrimers as well as glycodendrimers, have attracted great attention. [16][17][18][19][20] Such structures, in addition to the inherent branched structure of dendrimers, have the ability to self-assemble to form various nanostructures, including both conventional micelles 19 and liposome-like dendrimersomes. 21 The unique chemistry of calix-and thiacalix [4]arenes, consisting of the possibility of modification of both lower and upper rims, as well as the presence of four stereoisomers, made them a convenient platform to use both as a dendrimer's core [22][23][24][25][26][27] and as dendrones.…”
Section: Introductionmentioning
confidence: 99%